(untitled) (gjstudies, 2021)
This research investigates the underexplored causal relationship between specific public sector financial reporting reforms and tangible budgetary accountabilityoutcomes, moving beyond traditional compliance-based assessments. While priorliterature has extensively documented the implementation of accrual accountingand International Public Sector Accounting Standards (IPSAS), a significant gapexists in empirically linking the granular features of these reforms—such as thelevel of asset recognition, the treatment of social benefits, and the disclosure ofperformance information—to concrete changes in budgetary behavior, legislativeoversight efficacy, and public engagement. This study posits that the accountability impact of reporting reforms is not monolithic but is critically mediated bythe institutional architecture of the budget process and the political economy ofoversight actors. Employing a novel, cross-disciplinary methodological frameworkthat integrates quantitative fiscal panel data analysis with qualitative comparativecase studies rooted in political science and institutional economics, we examinea longitudinal dataset from 42 national governments over a 15-year period. Ourmethodology uniquely operationalizes ’accountability outcomes’ through a composite index measuring budget amendment responsiveness to audit findings, the variance between initial appropriations and final execution reports, and the frequency oflegislative hearings triggered by financial statement disclosures. The findings reveala non-linear and contingent relationship: reforms emphasizing service performancereporting and non-financial asset capitalisation show a stronger correlation with improved budgetary discipline in contexts with robust, non-partisan legislative budgetoffices. Conversely, the mere adoption of accruals, without complementary reformsto the budgetary classification system, shows negligible effects on accountability.The study makes an original contribution by deconstructing the ’black box’ of reporting reforms and providing a nuanced, evidence-based model for policymakersto design financial reporting systems that are not just technically sound but areinstitutionally calibrated to activate accountability mechanisms. This shifts thediscourse from a focus on accounting standards compliance to a strategic focus onthe informational needs of accountability actors within the public financial management ecosystem